2018
DOI: 10.1155/2018/5291945
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double Blind, Placebo Controlled, Parallel-Group Study to Evaluate the Safety and Efficacy of Curene® versus Placebo in Reducing Symptoms of Knee OA

Abstract: Background Curene® is a bioavailable formulation of turmeric  Curcucma longa extract comprising naturally derived curcuminoids formulated with proprietary Aquasome® technology. Curcuminoids were found to have anti-inflammatory properties by inhibiting Cyclooxygenase-2 (COX-2) and 5-lipoxygenase (5-LOX) enzyme and hence have potential application in the treatment of Osteoarthritis (OA). To evaluate the safety and efficacy of Curene® a randomized, double blind, placebo controlled, parallel-group study was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 9 publications
0
39
0
5
Order By: Relevance
“…Of the 10 RCT’s one did not provide gender data. 26 The remaining nine studies included 1237 participants, 340 men and 897 women. The mean age across the 10 studies was 56.85±9.19 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 10 RCT’s one did not provide gender data. 26 The remaining nine studies included 1237 participants, 340 men and 897 women. The mean age across the 10 studies was 56.85±9.19 years.…”
Section: Resultsmentioning
confidence: 99%
“…Of six studies comparing turmeric to placebo, five documented rescue therapy with NSAIDs or acetaminophen. 26–28 31 32 These five studies tracked the use of rescue therapy throughout their respected studies and reported an overall reduction in the use of rescue therapy in the turmeric group over placebo. Two studies compared turmeric to NSAID therapy for which rescue medication was not used.…”
Section: Assessment Of Methodological Quality and Risk Of Biasmentioning
confidence: 99%
“…The ability of boswellia (Boswellia serrata) and turmeric (Curcuma longa) extracts (alone or in combination) to relieve patients with KOA has been largely described in the literature [9][10][11][12][13][14][15][16][17][18][19][20]. However, to the best of our knowledge, this is the rst and unique study reporting data where their combination with red algae extracts is used.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies evaluating treatment effect in KOA usually focused on pain intensity and physical function [9][10][11][12][13][14][15][16][17][18][19][20]. In these studies, pain intensity was commonly assessed using a VAS and physical function using the Western Ontario McMaster Arthritis Index (WOMAC), a self-administered 24-item questionnaire [10,12,13,[15][16][17]20]. The WOMAC assessed activities of daily living, functional mobility, gait, general health and quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation